Pengaruh Profitabilitas dan Leverage terhadap Nilai Perusahaan pada Industri Makanan dan Minuman yang Terdaftar di Bursa Efek Indonesia dimasa Sebelum dan Sesudah Covid 19 (Periode 2018 –2022) - Papuania Lokobal; Wati Rosmawati; Ida Harahap (Akuntansi Pajak dan Kebijakan Ekonomi Digital, 2024)
This research aims to determine the effect of Profitability and Leverage on Company Value in the Food and Beverage Industry listed on the Indonesian Stock Exchange in the Pre and Post Covid 19 Period. This research uses quantitative methods, with secondary data obtained from the annual financial reports of the food and beverage industry listed on the Indonesia Stock Exchange for the 2018-2022 period. The population and sample in this research are the top 5 food and beverage industry companies listed on the Indonesia Stock Exchange during the 2018 - 2022 period. The sampling technique used the purposive sampling method. The analysis methods are descriptive statistics, classical assumption testing, multiple linear regression testing and hypothesis testing. The research results show that the Profitability and Leverage variables do not have a partial positive effect on Company Value. Meanwhile, the Profitability and Leverage variables do not have a positive effect on Company Value simultaneously.